The effect of CNQX on self-administration: present in nicotine, absent in methamphetamine model - Hrickova, Maria; Amchova, Petra; Ruda-Kucerova, Jana (Frontiers in Behavioral Neuroscience, 2024)
Objective: Addiction is a chronic disease with limited pharmacological options for intervention. Focusing on reducing glutamate levels in the brain seems to be a promising strategy in addiction treatment research. Our research aimed to evaluate the effects of CNQX, an antagonist that targets AMPA and kainate glutamatergic receptors while also exhibiting affinity for the NMDA receptor, especially by modulating its glycine site. We conducted this assessment on the self-administration of nicotine and methamphetamine via intravenous (IV) administration in rats.Methods: An operant IV self-administration model was used in male Wistar rats. When animals maintained a stable intake of nicotine or methamphetamine, we administered a single injection of CNQX (in the dose of 3 or 6 mg/kg IV) to evaluate its effect on drug intake. Subsequently, the rats were forced to abstain by staying in their home cages for two weeks. The period of abstinence was followed by a context-induced relapse-like session before which animals were pretreated with the injection of CNQX (3 or 6 mg/kg IV) to evaluate its effect on drug seeking.Results: CNQX significantly reduced nicotine intake during the maintenance phase, but no effect was revealed on nicotine seeking after forced abstinence. CNQX did not affect methamphetamine taking or seeking.The effect of reducing nicotine taking but not seeking could be explained by different involvement of glutamatergic receptors in various stages of nicotine dependence.